Aging of black men and women and the intransigent defense of social policies in the time of conservatism and ultraneoliberalism: contributions from social work (PerCursos, 2023)
In this article, as Social Work professionals, we express the uncompromising defense of the rights and politics that make up Brazilian social security based on the Constitution in force. We present the point of view adopted in our studies to analyze of the reality experienced by elderly workers emphasizing the old age of black population from Brazil. We transit through a brief exposition of conservatism and ultraneoliberalism, focusing on dissemination of ageism and on the content of public politics, more precisely, on social politics, for the dismantling and deregulation of rights obtained through social struggles. We emphasize some social indicators to argue about inequalities, as such as social determinations in the processes of aging of our populations. We exposed indicators that illustrate the question of old age of black people that are mostly users of social politics during the counter-reforms. We confront the responsibility and blaming of elderly and their families for old age in its tragic version and we give visibility to an important study, whose results indicate to the need to insert content on legislation to ensure the rights of elderly in stricto sensu postgraduate, in view of the contribution potential to the socialization of knowledge on the subject, a necessary mediation to change the life conditions of old black workers.
Keywords: aging; social politics; social work